Commitments and Contests: How Preferential Association Produces Equity. (September 2016) - Stovel, Katherine; Chiang, Yen-Sheng
This article offers a contribution to the broader theoretical goal of increasing our systematic understanding of the social mechanisms that underlie collective behavior. Specifically, we ask how it is possible that equity can arise in a market situation. Even though fair outcomes can be observed across a wide range of social situations that are not centrally coordinated, we argue that there is scant understanding of how these outcomes are facilitated and what impact they have on interaction patterns. We use experimental game theory to test two mechanisms of preferential association, which is defined as a situation where there is competition for partners and in which two actors have a preference for each other. The first mechanism, committed partnership, is abundant in social life and is exemplified by friendships. The second mechanism, competitive altruism, is the intuitive idea that to secure a desirable matching, one must display desirable behavior. To test the mechanisms, we use a laboratory experiment in which participants play a version of the well-known repeated Ultimatum Game. In our version of the game, players either (a) play each other randomly, (b) according to reputation, or (c) according to preferential association in which players are matched according to a preferred ranking of past player histories. The results suggest that fairness can arise from the reduced risk associated with committing to a desirable partner. This is a study of micro-to-micro mechanisms, investigating the micro-level conditions that produce a particular type of social action, namely, a sustainable equitable division of offerings.